Protective Capacity of Helichrysum italicum Infusion Against Intestinal Barrier Disruption and Translocation of Salmonella Infantis - Katja Kramberger; Katja Bezek Kranjc; Zala Jenko Pražnikar; Darja Barlič-Maganja; Saša Kenig (MDPI AG, 2024)
Background: Helichrysum italicum is a Mediterranean plant with well-known anti-inflammatory activity, but our previous whole transcriptome analysis has found that H. italicum infusion (HII) can also affect cytoskeletal rearrangement and tight junctions. The goal of the present study was to determine if HII improves the intestinal barrier (IB) dysfunction and by what mechanism. Methods: Caco-2 cells on Transwell inserts were used as a model of IB permeability. Heat-killed (HKB) or live Salmonella Infantis bacteria were used to induce IB integrity disruption upon three different testing conditions: pre-, co-, and post-treatment with 0.2 v/v% HII. Transepithelial electrical resistance values were used as an indicator of monolayer integrity before and after all treatments, and RT-PCR was used to assess the expression of tight junction proteins (TJPs) and inflammatory cytokines known to regulate intestinal permeability. Results: We found that all three treatments with HII improved the HKB-induced integrity disruption and decreased the down-regulation of TJP1, OCLN, and CLDN1, with the greatest effect observed in the pre-treated cells. Treatment with HII also decreased the up-regulation of CLDN2, TNF-α, IL-1β, and IL-6. In addition, pre-treatment of Caco-2 cells with HII prevented translocation of S. Infantis but did not prevent adhesion and invasion. Conclusion: This study showed that HII can improve inflammation-disrupted IB function by indirect modulation of mRNA expression of TJPs, especially in a preventive manner.